2012
DOI: 10.1373/clinchem.2011.180281
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Lipoprotein-Associated Phospholipase A2 Mass and Activity with Incident Vascular Events among Primary Prevention Patients Allocated to Placebo or to Statin Therapy: An Analysis from the JUPITER Trial

Abstract: BACKGROUND Although lipoprotein-associated phospholipase A2 (Lp-PLA2) levels are associated with cardiovascular events, Lp-PLA2 is physically linked to LDL cholesterol (LDL-C). Whether measures of Lp-PLA2 mass or activity continue to predict risk after LDL-C reduction by statin therapy is uncertain. METHODS Lp-PLA2 mass concentration and activity were evaluated at baseline and after treatment in the Justification for the Use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 25 publications
4
59
0
2
Order By: Relevance
“…Prior to the current study, several lines of evidence supported Lp‐PLA 2 activity as a risk indicator of adverse outcomes both in patients with stable CHD and in the general population in addition to being potentially involved in the development of atherosclerosis and vulnerable plaque at the tissue level 6, 7, 8, 9, 22, 23, 24, 25, 26, 27. Furthermore, in 2 case–control studies, natural deficiency of Lp‐PLA 2 activity due to carriage of the V279F‐null allele in the Lp‐PLA 2 gene was associated with a lower risk of developing CHD 30.…”
Section: Discussionmentioning
confidence: 74%
“…Prior to the current study, several lines of evidence supported Lp‐PLA 2 activity as a risk indicator of adverse outcomes both in patients with stable CHD and in the general population in addition to being potentially involved in the development of atherosclerosis and vulnerable plaque at the tissue level 6, 7, 8, 9, 22, 23, 24, 25, 26, 27. Furthermore, in 2 case–control studies, natural deficiency of Lp‐PLA 2 activity due to carriage of the V279F‐null allele in the Lp‐PLA 2 gene was associated with a lower risk of developing CHD 30.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, it is unlikely that failure to include these participants altered the results. Additionally, it has been reported that treatment with statins significantly lowers the Lp-PLA2 level 29) . In the current analysis, 11.8% of the subjects were receiving antidyslipidemic drugs, including statins, fibrates and traditional Chinese medicines for dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In addition, in the Long-Term Intervention with Pravastatin in Ischemic Disease (LIPID) study, among patients with stable chronic coronary heart disease, more than half the treatment effect of pravastatin in reducing rates of death from coronary heart disease or myocardial infarction was estimated to be due to an asso ciation with a reduction in levels of lipoprotein-associated phospholipase A 2 . 22 Incremental benefits of inhibiting lipoprotein-associated phospholipase A 2 activity, if present, could be less in patients treated with statins.…”
Section: Discussionmentioning
confidence: 99%